1996
DOI: 10.1182/blood.v88.6.2279.bloodjournal8862279
|View full text |Cite
|
Sign up to set email alerts
|

CD56+bright and CD56+dim natural killer cells in patients with chronic myelogenous leukemia progressively decrease in number, respond less to stimuli that recruit clonogenic natural killer cells, and exhibit decreased proliferation on a per cell basis

Abstract: Human natural killer cells (NK) require accessory cell-derived contact and soluble factors for maximal expansion. However, it is unclear whether increased recruitment of clonogenic NK, increased proliferation on a per cell basis, or a combination of both is responsible for the increased expansion. We show that expansion of both CD56+dim and CD56+bright NK from normal donors is increased in the presence of M2- 10B4 accessory cell-soluble factors. In contrast, the addition of M2- 10B4 stromal ligands further aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
2
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 32 publications
1
45
2
1
Order By: Relevance
“…Previously reported results indicate that NK cells of patients newly diagnosed with CML are reduced in numbers or in proportion among lymphocytes and have limited cytolytic capacity at diagnosis of CML, and that these abnormalities persist during IM-induced remission. (39)(40)(41) The present results suggest that NK cells are more sensitive to the residual BCR-ABL-positive cells than are NKT cells and CD8 + T cells. However, the patterns in CD8 + T cells were different from those in NK cells among the four groups, implying that these two types of immune cells play different roles in CML tumor surveillance in different situations.…”
Section: Discussionmentioning
confidence: 56%
“…Previously reported results indicate that NK cells of patients newly diagnosed with CML are reduced in numbers or in proportion among lymphocytes and have limited cytolytic capacity at diagnosis of CML, and that these abnormalities persist during IM-induced remission. (39)(40)(41) The present results suggest that NK cells are more sensitive to the residual BCR-ABL-positive cells than are NKT cells and CD8 + T cells. However, the patterns in CD8 + T cells were different from those in NK cells among the four groups, implying that these two types of immune cells play different roles in CML tumor surveillance in different situations.…”
Section: Discussionmentioning
confidence: 56%
“…The phenotypic and functional abnormalities of the immune system of CML patients have been well described (Spiers et al , 1977; Dowding et al , 1984; Tsuda & Yamasaki, 2000). Several reports have suggested that NK cells decrease in number and function during the course of CML, and are restored in accordance with a reduction in white blood cell counts (Pierson & Miller, 1996; Guarini et al, 2001). In the present study, expansion of NK/T cells was observed in both CML groups, when compared with the healthy control subjects.…”
Section: Discussionmentioning
confidence: 93%
“…CD27, CD11b and KLRG‐1 expression divides peripheral NK cells into subsets and available data suggest that cells expressing only CD27 + to be less differentiated than CD27 + CD11b + NK cells, and cells expressing CD11b and KLRG1, but not CD27, may represent the most differentiated NK cells (reviewed in 24, 25). Patients with diverse types of cancer (such as myelogenous leukemia and lung carcinoma) present with NK cell defects, including reduced NK cell numbers, reduced NK cell activity or reduced expression of activating receptors by NK cells 26, 27. Although clinical studies and reports using mouse tumor models have described MDSC suppressing NK cell activities 18, 28, 29, the role of specific MDSC subsets on NK cell suppression remains unclear.…”
Section: Introductionmentioning
confidence: 99%